PKM Pelatihan Numerasi Berdasarkan Ethnomatematika Di Jisda Yala Thailand - Panjaitan, Dedy Juliandri; Kartolo, Rahmad; Sari, Dwi Novita; Darmiati, Darmiati; Yusnita, Nora (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity was carried out at Jisda Yala Thailad. The learning process at Jisda Yala, Thailand has not been maximized in understanding ethnomathematics-based numeracy. This is because there is still little application of ethnomathematics-based numeracy. The biggest reason in this situation is the gap in understanding in solving ethnomathematics-based numeracy problems. The purpose of this service is that by training teachers to understand ethnomathematics-based numeracy, it is hoped that students at Jisda Yala, Thailand, will better understand ethnomathematics-based numeracy in the teaching and learning process. In the implementation of the program, the method of approach offered is a participatory approach. In the sense that the proposer team and partners are proactively involved in every activity. In addition, the solution approach used to solve the two main problems faced by partners is the implementation of inservice in the form of training and mentoring. The main target of the assistance is the understanding of numeracy based on ethnomathematics.